Lichen planus and Hepatitis C: a case-control study - Ghodsi, S Zahra (BioMed Central, 2004)
BACKGROUND: The association of lichen planus with hepatitis C (HCV) has been widely reported in the literature. However, there are wide geographical variations in the reported prevalence of HCV infection in patients with lichen planus. This study was conducted to determine the frequency of hepatitis C in Iranian patients with lichen planus at Razi hospital, Tehran. METHODS: During the years 1997 and 1998, 146 cases of lichen planus, 78 (53.1%) women and 69 (46.9%) men were diagnosed. They were diagnosed on the basis of the usual clinical features and, if necessary, typical histological findings. The patients were screened for the presence of anti-HCV antibodies by third generation ELISA and liver function tests. We used the results from screening of blood donors for anti HCV (carried out by Iranian Blood Transfusion Organization) for comparison as the control group. RESULTS: Anti-HCV antibodies were detected in seven cases (4.8%). This was significantly higher than that of the blood donors' antibodies (p < 0.001). The odds ratio was 50.37(21.45–112.24). A statistically significant association was demonstrated between erosive lichen planus and HCV infection. Liver function tests were not significantly different between HCV infected and non-infected patients. CONCLUSION: HCV apears to have an etiologic role for lichen planus in Iranian patients. On the other hand, liver function tests are not good screening means for HCV infection.